Dormancy of Macadamia Nut Seeds (Macadamia Integrifolia) by Drying and Soaking Water - Sondari, Nunung; Abdullah, Rohana; Amalia, Lia; Ulfah, Indriana; Azizah, Rifdah; Wilujeung, Sri (Ann Publisher, 2024)
Macadamia nut seeds are orthodox seeds that result in a dormancy period, so breaking the seed dormancy period is necessary. This study aims to determine the effect of drying and water immersion on dormancy breaking and macadamia bean seed germination and which drying and water immersion had the best impact on dormancy breaking and macadamia bean seed germination. The research was conducted in the soil laboratory and screen house of the Faculty of Agriculture, Winaya Mukti University, Tanjungsari District, Sumedang Regency, from June to November 2022. The experimental design used was a simple randomized block design (RBD) with a combination of drying and soaking seeds with nine treatment combinations. Each was repeated three times, so there were 27 experimental units. A = P 40oC + PA 45oC, B = P 45oC + PA 50oC, C = P 50oC + PA 55oC, D = P 50oC + PA 45oC, E = P 40oC + PA 50oC, F = P 45oC + PA 55oC, G = P 45oC + PA 45oC, H = P 40oC + PA 55oC, I = P 50oC + PA 50oC. The results showed that drying and soaking in water treatments at different temperatures had no significant effect on seed moisture content, seed cracking percentage, germination percentage, radicle length, and plumula length.